Use of Communication and Technology among Educational Professionals and Families - Kirstin Natale; Kathryn Lubniewski (International Electronic Journal of Elementary Education, 2018)
This study explored the perspectives of elementary school families and their preferences in communicating with their child’s teacher. The researchers utilized an online survey method which was distributed to the families of one elementary school. Survey questionsincluded areas of communication patterns, perceptions, and advice for improvement regarding communication between teachers and families. Results conclude that there are some discrepancies between family and teacher communication expectations. The intended purposes of these findings are to apply communication methods between stakeholders and families topotentially improve communication methods in schools